A Multiplex PCR for Simultaneous Detection of Three Zoonotic Parasites Ancylostoma ceylanicum, A. caninum, and Giardia lamblia Assemblage A. (31st August 2015) - Hu, Wei; Wu, Sheng; Yu, Xingang; Abullahi, Auwalu Yusuf; Song, Meiran; Tan, Liping; Wang, Zhen; Jiang, Biao; Li, Guoqing
Abstract : Ancylostoma ceylanicum, A. caninum, and Giardia lamblia assemblage A are common intestinal parasites of dogs and cats; they can also infect humans, causing parasitic zoonoses. In this study, a multiplex PCR method was developed for simultaneous identification and detection of those three zoonotic parasites. Three pairs of specific primers were designed based on ITS sequence of A. ceylanicum and A. caninum and TPI gene of G. lamblia available in the GenBank. The multiplex PCR reaction system was established by optimizing the reaction condition, and a series of tests on the sensitivity, specificity, and clinical application were also conducted. Results showed that three target fragments were amplified specifically; the detection limit was 10 eggs for both A. ceylanicum and A. caninum, 72 pg DNA for G. lamblia . Of 112 clinical fecal samples, 34.8% and 17.8% samples were positive for A. caninum and A. ceylanicum, respectively, while only 2.7% samples were positive for G. lamblia assemblage A. It is concluded that the established multiplex PCR assay is a convenient, rapid, cost-effective, and high-efficiency method for molecular detection and epidemiological investigation of three zoonotic parasites.